2007
DOI: 10.3989/revmetalm.2007.v43.i6.86
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-reinforcement reactivity in P/M titanium matrix composites

Abstract: La pulvimetalurgia siempre se ha mostrado como un proceso viable en la producción de componentes complejos con una minimización de la mecanización posterior de los mismos, por lo que representa una fuerte reducción de los costes de producción [1] . Esto se aplica en particular a materiales relativamente caros como las aleaciones de titanio [2 y 3] , donde resulta fundamental la minimización de las perdidas por mecanizado. Inicialmente, la pulvimetalurgia se ha considerado un método para la producción económic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…Though Ti-rich Si alloy production has been demonstrated through alternative powder metallurgy routes, there are very few reports in the literature exploring these, with some notable exceptions. Amigo´et al [25,26] investigated Ti and TiSi 2 powder vacuum sintering between 1150°C and 1315°C and found that the Ti matrix reacts with TiSi 2 particles to produce Ti-Si and Ti 5 Si 3 intermetallic compounds. Pribytkov et al [27] studied Ti, Si, and Ti 5 Si 3 powder vacuum sintering at 1250°C, and reported the presence of a-Ti, Ti 5 Si 3 , and Ti 5 Si 4 alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Though Ti-rich Si alloy production has been demonstrated through alternative powder metallurgy routes, there are very few reports in the literature exploring these, with some notable exceptions. Amigo´et al [25,26] investigated Ti and TiSi 2 powder vacuum sintering between 1150°C and 1315°C and found that the Ti matrix reacts with TiSi 2 particles to produce Ti-Si and Ti 5 Si 3 intermetallic compounds. Pribytkov et al [27] studied Ti, Si, and Ti 5 Si 3 powder vacuum sintering at 1250°C, and reported the presence of a-Ti, Ti 5 Si 3 , and Ti 5 Si 4 alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Este tipo de unión puede existir en el caso de refuerzos que tengan la superficie rugosa. La ausencia de unión química conduce a un material compuesto con propiedades mecánicas mediocres (Amigó et al 2007).…”
Section: La Interfase Matriz/refuerzounclassified